Legal representation and trial outcomes: a bourdieusian analysis of chinese criminal court practices - He, Ni (Crime, law and social change, 2016)
Based on a rare survey of criminal justice practitioners from one large coastal province in China, this study provides an application of Bourdieusian sociology of juridical practice in Chinese criminal courts. We test whether and how criminal trial outcomes can be predicted by using variables measuring various forms of Bourdieusian capital. We found that measurements based on self-reported efficacy of legal representation practices during the pretrial and trail stages (as activated judicial capital), more so than those indicating respondents’ personal and professional statuses (either inherited or acquired capital), yield greater and more consistent impact on the trial outcomes. Implications for future theory, methodology and Chinese rule of law reform are discussed.